Analisis Bibliometrik Modal Sosial dalam Konteks Pembangunan Berkelanjutan di Indonesia - Syahrier, Fajar Alan; Putra, Dinda Syufradian; Anshori, M. Wira; Nugroho, Sapto Setyo (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2025)
This study aims to conduct a bibliometric analysis of social capital in the context of sustainable development in Indonesia. This study covers scientific publications from 2020 to 2025 using bibliometric data obtained from the Scopus database. The analysis included visual mapping of keyword networks, identification of key research trends, leading researchers, and linkages between themes such as community, policy, economic growth, and environment. The findings show that social capital is closely linked to strategic issues such as community participation, governance, and multi-stakeholder collaboration in supporting sustainability. This research is expected to contribute significantly to developing academic discourse and policy practice on social capital-based sustainable development in Indonesia.